Design and Analysis of Back Lifting Mechanism of Modular Multifunctional Nursing Bed - Dianxing Xu; Hui Fang; Li Wang; Ping Yuan (Jixie chuandong)
In response to the needs of the health care industry，based on the modular design method，the multifunctional nursing bed is divided into modules and functions are analyzed，and the overall plan design of the multifunctional nursing bed is completed. Based on the principle of ergonomics，the back lifting mechanism is researched. By analyzing and comparing the advantages and disadvantages of the existing back lifting mechanism，a two-fold back lifting mechanism is designed，and the corresponding mathematical model of motion is established. With the help of Matlab,the theoretical motion analysis is carried out, and it is compared with the simulation results of Adams kinematics to verify the rationality of the mechanism design. With the help of Ansys，a finite element analysis is carried out on the key components of the back lifting mechanism to ensure the safety of the mechanism，and an experimental prototype was made for verification.